Mechanisms and bases of resistance in maize to mites - Archer, T.L.=700 1 Peairs, F.B.; Mihm, J.A.
Sumario (En)
Ilus.; 12 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; GERMOPLASMA; POLINIZACION; INVESTIGACION; RESISTENCIA A PRODUCTOS QUIMICOS